Dual observer-based compensators for nonlinear systems - Deutscher, Joachim (International Journal of Robust and Nonlinear Control, 2014)
In this article, the concept of dual observer-based compensators is extended from linear to nonlinear systems. It is shown that a dual observer-based compensator achieves stabilization by rendering an invariant manifold attractive in which desired dynamics can be assigned. The design of these compensators for nonlinear systems is considerably simple if a flat output of the system to be controlled is known which is illustrated by means of a simple example. Copyright © 2012 John Wiley & Sons, Lt
Keywords: flatness; linearization; nonlinear systems; output feedback; stabilization